Looking after yourself: Clinical understandings of chronic-care self-management strategies in rural and urban contexts of the United Kingdom and Australia - Carr, Susan Mary (SAGE Open Med, 2014)
OBJECTIVES: This article reports on the outcomes of two similar projects undertaken during 2011–2012 in Australia (Rural Northern New South Wales) and the United Kingdom (Urban Northern United Kingdom) that sought to identify the strategies that health professionals employ to actively involve patients with chronic conditions in the planning and delivery of their care. In particular, this study explored understandings and contexts of care that impacted on the participants’ practices. This study was informed by the global shift to partnership approaches in health policy and the growing imperative to deliver patient or client-centred care. METHODS: An ethnomethodological design was used, as ethnomethodology does not dictate a set of research methods or procedures, but rather is congruent with any method that seeks to explore what people do in their routine everyday lives. Focus groups and interviews were employed to explore the strategies used by a range of primary health-care providers, such as general practitioners, nurses, social workers, diabetes educators, dieticians and occupational therapists, to support clients to effectively manage their own chronic conditions. RESULTS: Data from both studies were synthesised and analysed thematically, with the themes reflecting the context, similarities and differences of the two studies that the participants felt had either facilitated or blocked their efforts to support their clients to adopt self-care strategies. CONCLUSION: Supporting patients/clients to engage in actively self-managing their health-care needs requires changes to clients’ and clinicians’ traditional perspectives on their roles. The barriers and enablers to supporting clients to manage their own health needs were similar across both locations and included tensions in role identity and functions, the discourse of health-care professionals as ‘experts’ who deliver care and their level of confidence in being facilitators who ‘educate’ clients to effectively manage their health-care needs, rather than only the ‘providers’ of care.